AN ANALYSIS OF SPEAKING DIFFICULTIES FACED BY THE SECOND SEMESTER STUDENTS IN THE ENGLISH EDUCATION STUDY PROGRAM AT JAMBI UNIVERSITY ACADEMIC YEAR 2023/2024 - Fadlan, Muhamamd; Masita, Ella; Volya, Duty (Universitas Jambi, 2025)
Speaking is often one of the fears when learning a language, including for undergraduate students. They will find some difficulties that hamper their ability to explore their abilities in speaking English. This research was conducted to explain the speaking difficulties faced by English education study students at Jambi University, as categorized and not categorized by Penny Ur theory. This research used a qualitative case study design. The researcher chose seven second-semester students in the English education study program at Jambi University as participants. In collecting data, the researcher used a semi-structured interview. The result is according to the theory, but one finding is not an identity in the theory. The research has found that every student had different difficulties in speaking; there were inhibitions, nothing to say, low or uneven participation, and mother tongue use. Students had factors that caused difficulties in speaking English. Most of these problems are due to a lack of grammar and vocabulary.